2013
DOI: 10.1063/1.4813110
|View full text |Cite
|
Sign up to set email alerts
|

Stray field enhanced vortex dissipation in YBa2Cu3O7/La0.7Sr0.3MnO3/YBa2Cu3O7 hetero-epitaxial tri-layer

Abstract: In this work, we report observation of two superconducting transitions and their response to an external field in pulsed laser deposited YBa2Cu3O7/La0.7Sr0.3MnO3/YBa2Cu3O7 (Y-L-Y) hetero-epitaxial tri-layer. Magnetization data of Y-L-Y tri-layer in “out-plane” geometry showed a single Meissner transition indicating superconductivity of the top and bottom YBa2Cu3O7 layers to be magnetically coupled. In contradiction, the magneto-transport data unusually showed two transition onsets Tcon1 and Tcon2 implying elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…The experiments performed in this study are analogous to a series of results reported in many important studies [1][2][3][4][5][6]18]. The main difference lies in the measuring parameter employed and the information that it provides.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…The experiments performed in this study are analogous to a series of results reported in many important studies [1][2][3][4][5][6]18]. The main difference lies in the measuring parameter employed and the information that it provides.…”
Section: Discussionmentioning
confidence: 74%
“…Hybrid structures composed of ferromagnetic (F) and super conducting (S) thin films have been the subject of extensive experimental and theoretical work. Typical results deal mainly with variations in the resistance (R) and critical the temper ature (T c ) of the superconducting state under the influence of an F layer [1][2][3][4]. Recently, these hybrid systems have been observed to sustain spinpolarized supercurrents if triplet pairing of electrons is promoted by the addition of a non collinear ferromagnetic film at the S/F interface [5,6].…”
Section: Introductionmentioning
confidence: 99%